The influence of foreign and domestic stimulants on the medium-fiber variety of cotton Andijan-35 (Texas Journal of Agriculture and Biological Sciences, 2023)
Namangan region has a positive effect on the germination of medium-fibrous acorns Andijan35 in conditions of hungry rich soils, stimulants albite and gummi 20, sprouts in the field, albite 75 ml / t and gummi 20 when applied in the norms of 1.0 l/t 14.8-17.9; 11.3-15.6%, has a positive effect on root rot and gommosis, the height of the acorn is 1.4-10.6 cm, the number of branches of the culture is 0.2-1.2 grains, and the number of acorns is 0.6-1.8 grains, the flowering rate is 7.0-14.2%, the opening of acorns is 11.2-16.0%, the number of leaves due to one plant was equal to 5.4-14.3 grains, 34.1-224.4 when the leaf surface is illuminated, 260.1-670.8 during flowering and 260.6-681.6 cm2 in height during and that cotton yields increased by 4.9-5.5 c/ha compared to control.